2014
DOI: 10.3389/fnins.2014.00231
|View full text |Cite
|
Sign up to set email alerts
|

Sexual attractiveness of male chemicals and vocalizations in mice

Abstract: Male-female interaction is important for finding a suitable mating partner and for ensuring reproductive success. Male sexual signals such as pheromones transmit information and social and sexual status to females, and exert powerful effects on the mate preference and reproductive biology of females. Likewise, male vocalizations are attractive to females and enhance reproductive function in many animals. Interestingly, females' preference for male pheromones and vocalizations is associated with their genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 177 publications
(231 reference statements)
1
78
0
1
Order By: Relevance
“…Efferents from AOB mitral cells project to the medial amygdala, which has been shown to transmit olfactory information implicated in social and reproductive behaviour to the hypothalamus in rodents (Asaba et al. ). The posteromedial cortical amygdala nucleus (PMCo) (Figs 6.2 to 7.1) also receives direct projections from the AOB and may play a role in odour‐guided aspects of reproductive behaviour (Scalia & Winans, ; Segovia et al.…”
Section: Methodsmentioning
confidence: 99%
“…Efferents from AOB mitral cells project to the medial amygdala, which has been shown to transmit olfactory information implicated in social and reproductive behaviour to the hypothalamus in rodents (Asaba et al. ). The posteromedial cortical amygdala nucleus (PMCo) (Figs 6.2 to 7.1) also receives direct projections from the AOB and may play a role in odour‐guided aspects of reproductive behaviour (Scalia & Winans, ; Segovia et al.…”
Section: Methodsmentioning
confidence: 99%
“…There are both pheromonal and ultrasonic cues to prevent in-breeding, and unlike rats, both male and female mice disperse at puberty (Bronson, 1979;Asaba et al, 2014). …”
Section: B Behavioral Ecology Of Rats and Micementioning
confidence: 99%
“…We used a controlled cage setup to balance between the advantage of allowing sensory cues (which mice could use for individual assessment and potential mate choice [16, 46]) and the aim of not producing unwanted offspring for ethical reasons. It has been shown that social preferences measured in lab experiments do not necessarily lead to a higher number of matings between social partners [50, 51, 59, 60].…”
Section: Discussionmentioning
confidence: 99%